Hard X-ray cataclysmic variables. Issue 5 (1st September 2020) - de Martino, D.; Bernardini, F.; Mukai, K.; Falanga, M.; Masetti, N.
Abstract: Among hard X-ray Galactic sources detected with the Swift and INTEGRAL surveys, those discovered as accreting white dwarf binaries have surprisingly boosted in number in the recent years. The majority are identified as magnetic Cataclysmic Variables of the Intermediate Polar type, suggesting this subclass as an important constituent of the Galactic population of X-ray sources. We here review and discuss the X-ray emission properties of newly discovered sources in the framework of an identification programme with the XMM-Newton satellite that increased the sample of this subclass by a factor of two.